2017
DOI: 10.1186/s12610-017-0054-y
|View full text |Cite
|
Sign up to set email alerts
|

“This is where it all started” – the pivotal role of PLCζ within the sophisticated process of mammalian reproduction: a systemic review

Abstract: Mammalian reproduction is one of the most complex and fascinating biological phenomenon, which aims to transfer maternal and paternal genetic material to the next generation. At the end of oogenesis and spermatogenesis, both haploid gametes contain a single set of chromosomes ready to form the zygote, the first cell of the newly developing individual. The mature oocyte and spermatozoa remain in a quiescent state, during which the oocyte is characterized by nuclear and cytoplasmic arrest, while the spermatozoa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Lastly, the C2 C-terminal domain of PLCζ is crucial for the function of PLCζ involved in targeting proteins to cell membranes. It has been shown that although the deletion of the C2 domain results in a partial loss of enzymatic activity, it has no impact on the enzyme's Ca 2+ sensitivity in vitro [16]. The mechanism of PLCZ signaling begins with the PLCζ diffusion in the ooplasm after the fusion of spermatozoa within the oocytes.…”
Section: The Plcζ Mechanism Of Actionmentioning
confidence: 99%
“…Lastly, the C2 C-terminal domain of PLCζ is crucial for the function of PLCζ involved in targeting proteins to cell membranes. It has been shown that although the deletion of the C2 domain results in a partial loss of enzymatic activity, it has no impact on the enzyme's Ca 2+ sensitivity in vitro [16]. The mechanism of PLCZ signaling begins with the PLCζ diffusion in the ooplasm after the fusion of spermatozoa within the oocytes.…”
Section: The Plcζ Mechanism Of Actionmentioning
confidence: 99%
“…5 In mammals, this intracellular Ca 2+ signal is delivered in the form of a series of waves of intracellular Ca 2+ (oscillations) that begins shortly after fusion of the gametes and persists until completion of meiosis. 6 These oscillations release the oocyte from metaphase 2 meiotic arrest and initiate embryogenesis, cortical granule exocytosis, sperm nucleus decondensation, recruitment of maternal mRNA, and pronuclear development, a series of events termed “oocyte activation.” 7…”
Section: Oocyte Activationmentioning
confidence: 99%
“…6 These oscillations release the oocyte from metaphase 2 meiotic arrest and initiate embryogenesis, cortical granule exocytosis, sperm nucleus decondensation, recruitment of maternal mRNA, and pronuclear development, a series of events termed "oocyte activation." 7…”
Section: Oocyte Activationmentioning
confidence: 99%
“…In all mammalian species studied, fertilization results in a series of intracellular calcium (Ca 2+) increases, referred to as oscillations, triggered by PLCζ , responsible for driving oocyte activation ( Bedford-Guaus et al, 2011 ). The oscillation of Ca 2+ levels plays an essential role in early embryonic development ( Gat and Orvieto, 2017 ). Lower RNA expression of PLCζ and protein levels was observed in teratozoospermic infertile men when compared with fertile patients ( Azad et al, 2018 ; Kamali-Dolat et al, 2016 ); however, no differences were detected in localization patterns ( Azad et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%